A Study of Gene Xpert in Screening of Sputum in HIV Positive Patients Presenting to Tertiary Care Centre - Bansal, Deepak; Avashia, Sanjay; Karothiya, Mitesh (National Journal of Community Medicine, 2016)
Introduction: Present study was conducted to study Gene Xpert in screening of sputum in HIV positive patients, to estimate the burden of drug resistance TB in HIV patients and to estimate the prevalence of MDR TB in HIV positive patients. Methods: RNTCP is currently using Gene Xpert to screen all HIV positive patients to diagnose pulmonary TB and rifampicin resistance. In this study, pulmonary samples referred to state level intermediate reference laboratories (IRLs) Indore between January 2015 to December 2015 were investigated and subjected to Gene Xpert. Results: A total of 3033 pulmonary specimens were included in the study undergoing Gene Xpert; out of which 604 specimens were from HIV positive patients. In 85 (14.07%) HIV positive patients (out of 604) MTB was detected and RIF was sensitive (14.07%). In 06 (0.99%) HIV positive patients MTB, was detected and RIF resistance was found. Conclusion: Screening of pulmonary samples with Gene Xpert in all HIV positive patients has enormous scope in early diagnosis and treatment of TB in terms of active case finding of patients with drug resistant tuberculosis. The results are available in less than 2 hours. This leads to less transmission of disease with reduced morbidity.